Domestication: A Case Study of Red Jungle Fowl Coops Management by the Communities in Bengkulu - J. Setianto; Sutriyono Sutriyono; H. Prakoso; B. Zain (Universitas Bengkulu, 2018)
Red junglefowl domestication has been carried out by communities in the region of Bengkulu Province. This research aimed to study the management of keeping red junglefowl and the offsprings and the coops. The research was carried out in Bengkulu Province. The sample of breeders was selected using snow-ball sampling method. The selected samples were recorded and used as the data and information sources. The data were collected by interviewing, questionnaires, and direct observation. The data obtained were processed, presented in the form of tables, drawings and analyzed descriptively. Based on research method, out of a total of 200 red junglefowl breeders and or the offsprings were chosen 50 (25%) respondents from Bengkulu city, 50 (25%) respondents from Seluma District, 50 (25%) respondents from Central Bengkulu District and 50 (25%) respondents from North Bengkulu District. The red junglefowl and the offsprings breeding is divided into keeping the hens, roosters and chicks. The hens were kept in the coop during the day and night (41%), released during the day and night (22%) and kept during the night in the coop and released during the day (37%). In the same way, in sequence, the breeding of roosters was 71%, 12.5% and 16.5%, while the breeding of chicks was 37%, 18% and 45%. 31% respondents provided quarantine coop, while 69% respondents did not. 75% provided hens coop and 25% did not, 61% provided roosters coop and 39% did not. Finally, the respondents who provided chicks coop were 40.5% and 59.5% did not. The breeding management has not been done intensively, some respondents have completed coops system, but not yet meet the criteria of good coop.Keywords: Domestication, red junglefowl, coops